2012
DOI: 10.1016/j.rdc.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Spondyloarthritis

Abstract: Synopsis Spondyloarthritis (SpA) represents a group of interrelated diseases with common clinical features and a close association with HLA-B27. Figures on the incidence and prevalence of diseases vary highly dependent on methodological differences between studies, the case definition used to classify disease and on the prevalence of HLA-B27 in the population studied. When summarizing the available literature, incidence rates of SpA are mainly based on the ESSG criteria and range between 0.48 and 63/100.000 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 86 publications
6
125
0
1
Order By: Relevance
“…In developed countries, a large number of publications are available on the prevalence of RA and SpA. 1,2 However, in low-and middle-income countries, studies on RA and SpA are sparse. Likewise, in Turkey, epidemiological studies regarding RA and SpA reported to date are very few and regional, rather than nationwide.…”
Section: Prevalence Of Rheumatoid Arthritis and Spondyloarthritis Inmentioning
confidence: 99%
“…In developed countries, a large number of publications are available on the prevalence of RA and SpA. 1,2 However, in low-and middle-income countries, studies on RA and SpA are sparse. Likewise, in Turkey, epidemiological studies regarding RA and SpA reported to date are very few and regional, rather than nationwide.…”
Section: Prevalence Of Rheumatoid Arthritis and Spondyloarthritis Inmentioning
confidence: 99%
“…Laps and Eskimos have a prevalence of 15e25% and Haida Indians of 50%. There is a relationship between the prevalence of HLA B27 and the prevalence of AS in these populations [40].…”
Section: Hla B27mentioning
confidence: 99%
“…The Rome criteria were based on expert opinion and allowed classification of patients based on fulfillment of either clinical or imaging criteria. When later evaluated in a population study, the role of the radiographs in showing sacroiliac (SI) joint changes characteristic of AS was found to be unsatisfactory [5]. This led to a revision of the Rome criteria and the creation of the New York (NY) criteria in 1966, which required radiologic evidence of sacroiliitis for fulfillment of the criteria and diagnosis of AS.…”
Section: Nomenclature and Classification Criteriamentioning
confidence: 99%
“…The mNY criteria have been the most widely used in clinical and epidemiological studies and remain an important part of the radiologic arm of the modern ASAS criteria. The main restriction of these criteria is their requirement of radiologic evidence of sacroiliitis, which limits the sensitivity in the diagnosis of early axSpA when radiologic damage may not yet be present, thus delaying the diagnosis up to 8 years [5].…”
Section: Nomenclature and Classification Criteriamentioning
confidence: 99%
See 1 more Smart Citation